66.7k views
0 votes
Simplify the expression –3(x + 3)2 – 3 + 3x. What is the simplified expression in standard form?

2 Answers

3 votes

Answer:
-3x^2-15x-30

Explanation:

We need to remember that
(a\±b)^2=a^2\±2ab+b^2

Knowing this, we can simplify the expression:


-3(x + 3)^2 - 3 + 3x=-3[x^2+2(x)(3)+3^2]-3+3x=-3[x^2+6x+9]-3+3x

Apply Distributive property:


=-3x^2-18x-27-3+3x

Add like like terms:


=-3x^2-15x-30

Since it has the form
ax^2+bx+c, it is already expressed in Standad form.

User Cellcortex
by
5.4k points
4 votes

For this case we must simplify the following expression:


-3 (x + 3) ^ 2-3 + 3x

We solve the parenthesis:


-3 (x ^ 2 + 2 (x) (3) + 3 ^ 2) -3 + 3x =\\-3 (x ^ 2 + 6x + 9) -3 + 3x =

We apply distributive property to the terms within parentheses:


-3x ^ 2-18x-27-3 + 3x =

We add similar terms:


-3x ^ 2-18x + 3x-27-3 =\\-3x ^ 2-15x-30

Answer:


-3x ^ 2-15x-30

User Ali Arslan
by
5.7k points